APLIKASI KAMUS BAHASA DAERAH DENGAN ALGORITMA LEVENSHTEIN DISTANCE BERBASIS ANDROID - Ahmad Thariq (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
Maluku has several local languages, one of which is asilulu language. Where the use of asilulu language in daily communication has decreased due to many people who prioritize slang. Preservation of local languages is very important considering the rapid advancement of technology today. Therefore, it is necessary to create an application that can fulfill every user's desire for a portable book replacement’ that can be used anytime and anywhere. Dictionary application media can be a solution to introduce asilulu language to the wider community. The purpose of this research is to create a dictionary application to facilitate the learning process of asilulu regional language and help them find vocabulary in Indonesian - asilulu effectively and efficiently. In addition, word spelling errors often occur in language dictionary software, which can make it difficult for us to find information. The solution to this problem is to use the levenshtein distance algorithm to make it easier to find words in language dictionary applications. The levenshtein distance method is the method used in this research while for software development it uses the waterfall model. This application is made using mysql as a database, for tools using android studio and programming language using java. Levenshtein distance testing in this application can improve keyword searches for terms that are wrong in writing in the test this application can run smoothly. The results of this application can be a useful medium for learning, preserving and developing asilulu regional languages to be preserved as language wealth.